Afinal, o que os dados mostram sobre a atuaç\~ao das ONGs? Análise de transferências federais e projetos executados pelas organizaç\~oes da sociedade civil no Brasil - Janine Mello; Ana Camila Ribeiro Pereira; Pedro Gomes Andrade (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The article aims to contribute for studies related to civil society organizations and their fields of action analyzing the public monetary resources received by them and the projects executed by these organizations in partnership with federal government in Brazil. The aim is to detail how organizations executed the resources received from 2010 to 2018 considering aspects as organization profile, general characteristics of projects developed, thematic areas and the evolution of these partnerships in recent years. For that were considered information from the public platform Mapa das Organizaç\~oes da Sociedade Civil (Mapa das OSCs) e from Brazilian federal public budget (2010-2018).
Keywords: L31; 330; OSCs; public monetary resources; third sector